AN ANALYSIS OF STUDENTSâ ABILITY IN USING CONDITIONAL SENTENCES OF THE SIXTH SEMESTER STUDENTS IN ENGLISH DEPARTMENT OF TARBIYAH FACULTY IAIN ANTASARI - Saadillah, Saadillah; Herlena, Herlena (English Department of Faculty of Tarbiyah and Teachers Training, 2014)
This researchÂ describes the ability in using conditional sentences of the sixth semester students in English Department of IAIN Antasari academic year 2011/2012. The problemsÂ in this research are: 1) how is studentsâ ability in using conditional sentences? Â 2) what is the most studentsâ common error in using conditional sentences? This study areÂ supposed to know the studentsâ ability in using conditional sentencesÂ and the most studentsâ common errors in using conditional sentences. The subjects in this research are 69Â of 79Â students in the English Department of IAIN Antasari in academic year 2011/2012.Â The objects of this research are the ability in using conditional sentences of the sixth semester students in the English Department of IAIN Antasari Academic Year 2011/2012 and the most studentsâ common errors in using conditional sentences.Â The data are collected by using some techniques. They are: written test, observation, interviewÂ and documentary.Â Data processing in this research is divided into four stages, they are checking, scoring, tabulatingÂ and interpreting. Then all data are analyzed descriptively and use inductive method to make conclusion. Â The result of the research denoted that the level of studentsâ ability in using conditional sentences is in fair category. It is based on calculation it is mean that is 64,Â 8. After analyzing each type of test, the writer found that the most studentsâ common errors is in type III (41,6%).Â It can be concluded that mistakes happened because the students do not understand well about tenses that is used in conditional sentences. For example, type I we use simple present tense, type II we have to use simple past tense, and for type III we need know well about past perfect tense. The writer also concludes, the mistakes that the students have done because inappropriate in choosing modal. The students have to choose which appropriate modal should be attached to the sentence.